The docking protein p130Cas regulates cell sensitivity to proteasome inhibition - Zhao, Ming (BioMed Central, 2011)
BACKGROUND: The focal adhesion protein p130Cas (Cas) activates multiple intracellular signaling pathways upon integrin or growth factor receptor ligation. Full-length Cas frequently promotes cell survival and migration, while its C-terminal fragment (Cas-CT) produced upon intracellular proteolysis is known to induce apoptosis in some circumstances. Here, we have studied the putative role of Cas in regulating cell survival and death pathways upon proteasome inhibition. RESULTS: We found that Cas-/- mouse embryonic fibroblasts (MEFs), as well as empty vector-transfected Cas-/- MEFs (Cas-/- (EV)) are significantly resistant to cell death induced by proteasome inhibitors, such as MG132 and Bortezomib. As expected, wild-type MEFs (WT) and Cas-/- MEFs reconstituted with full-length Cas (Cas-FL) were sensitive to MG132- and Bortezomib-induced apoptosis that involved activation of a caspase-cascade, including Caspase-8. Cas-CT generation was not required for MG132-induced cell death, since expression of cleavage-resistant Cas mutants effectively increased sensitivity of Cas-/- MEFs to MG132. At the present time, the domains in Cas and the downstream pathways that are required for mediating cell death induced by proteasome inhibitors remain unknown. Interestingly, however, MG132 or Bortezomib treatment resulted in activation of autophagy in cells that lacked Cas, but not in cells that expressed Cas. Furthermore, autophagy was found to play a protective role in Cas-deficient cells, as inhibition of autophagy either by chemical or genetic means enhanced MG132-induced apoptosis in Cas-/- (EV) cells, but not in Cas-FL cells. Lack of Cas also contributed to resistance to the DNA-damaging agent Doxorubicin, which coincided with Doxorubicin-induced autophagy in Cas-/- (EV) cells. Thus, Cas may have a regulatory role in cell death signaling in response to multiple different stimuli. The mechanisms by which Cas inhibits induction of autophagy and affects cell death pathways are currently being investigated. CONCLUSION: Our study demonstrates that Cas is required for apoptosis that is induced by proteasome inhibition, and potentially by other death stimuli. We additionally show that Cas may promote such apoptosis, at least partially, by inhibiting autophagy. This is the first demonstration of Cas being involved in the regulation of autophagy, adding to the previous findings by others linking focal adhesion components to the process of autophagy.